Functional implications of MIR domains in protein O-mannosylation - Chiapparino, Antonella; Grbavac, Antonija; Jonker, Hendrik RA; Hackmann, Yvonne; Mortensen, Sofia; Zatorska, Ewa; Schott, Andrea; Stier, Gunter; Saxena, Krishna; Wild, Klemens; Schwalbe, Harald; Strahl, Sabine; et al. (eLife, 2020)
Protein O-mannosyltransferases (PMTs) represent a conserved family of multispanning endoplasmic reticulum membrane proteins involved in glycosylation of S/T-rich protein substrates and unfolded proteins. PMTs work as dimers and contain a luminal MIR domain with a β-trefoil fold, which is susceptive for missense mutations causing α-dystroglycanopathies in humans. Here, we analyze PMT-MIR domains by an integrated structural biology approach using X-ray crystallography and NMR spectroscopy and evaluate their role in PMT function in vivo. We determine Pmt2- and Pmt3-MIR domain structures and identify two conserved mannose-binding sites, which are consistent with general β-trefoil carbohydrate-binding sites (α, β), and also a unique PMT2-subfamily exposed FKR motif. We show that conserved residues in site α influence enzyme processivity of the Pmt1-Pmt2 heterodimer in vivo. Integration of the data into the context of a Pmt1-Pmt2 structure and comparison with homologous β-trefoil - carbohydrate complexes allows for a functional description of MIR domains in protein O-mannosylation.
Gesehen am 17.02.2022